Education and Cooking Demonstration of Supplementary Food for Toddlers as an Effort to Prevent Stunting in Pegiringan Village, Bantarbolang District, Pemalang Regency - Singgih Setiawan; Arditya Prayogi (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
Stunting is one of the public health problems that is still a serious concern in Indonesia, including in Pegirigan Village, Bantarbolang District, and Pemalang Regency. The decline in nutritional quality during the first 1000 days of life (DOL) is one of the leading causes of stunting. This article aims to describe the stunting prevention efforts carried out in Pegirigan Village, focusing on interventions involving families, communities, and the health sector. The method used in this research is a qualitative descriptive approach with data collection through interviews, observations, and documentation involving health workers, posyandu cadres, and families with toddlers in Pegirigan Village education. The results showed that stunting prevention efforts in this village have included educating children about healthy eating patterns, the importance of exclusive breastfeeding, monitoring child growth, and providing supplementary food for at-risk children. In addition, the active role of posyandu cadres and support from the local government is significant in increasing public awareness about the importance of good nutrition in preventing stunting. However, there are still challenges regarding resource availability and lack of family participation in stunting prevention programs. Therefore, it is necessary to increase coordination between the health, education, and community empowerment sectors to address this problem more effectively.